FOOD POLICY COUNCIL AS CIVIC ENGAGEMENT FOR FOOD ISSUES - Masashi Tachikawa (Journal of Asian Rural Studies, 2017)
The purpose of this paper is to elucidate the nature of food issue in our society and propose a forum to discuss multi-facet issues of food based on the North American experience, such as food policy council (FPC). Contemporary food system in Japan is full of problems, such as low level self-sufficiency, food loss, problem of food access, large food miles, declining food culture under globalization, and so on. After reviewing these food related issues, the paper refers to the US and Canadian experiences on food policy council as a model to provide a forum for various stakeholders with different or even conflicting interests. Based on observations on the FPCs, such as Knoxville (US) and Toronto (Canada), author emphasized public aspect of food issues and draw attentions to differences in structural aspects of food between North America and Japan. The paper also tries to draw attention to differences between North America and Japan in terms of food issues. In particular, the demographic and geographical differences would exist of a major structural aspect when considering food issue in Japan.